Indonesian Language Teaching Based on Internet of Things (IOT) in Archipelago - Muzaki, Ferril Irham (Universitas Negeri Malang, 2019)
Abstract: This study aims to (1) analyze the study of learning theory that is suitable to be applied in the archipelago in Indonesia, (2) conduct an analysis of the application of Mobile Learning -based learning in the learning process in the archipelago and (3) study the use of the Internet of Things (IoT ) on Indonesian language material in the archipelago. The method used is ethnographic research by taking islands in the East Java region that enter the Java Sea. The results of this study are (1) the application of Mobile Learning despite focusing on IoT, which pays attention to the availability of infrastructure, (2) Mobile Learning -based learning despite paying attention to learning designs that focus on offline learning media and (3) Mobile Learning -based learning even though directed students Centered Method in the development of Mobile Learning based learning. It is recommended to stakeholders to diversify the learning process.